Conceptions and Practices of health professionals facing sexual and gender diversity in healthcare services: an integrative review (Research, Society and Development, 2022)
The approaches and discussions of gender constituted, in principle, in the social sciences are of great relevance in the understanding of the roles socially constructed for men and women and, at the same time, it is a phenomenon of political discussion and socio-historical implication that demands new configurations in the forms of assistance and in the conceptions of care in health services. In this perspective, the objective of this article was to investigate, in the national literature, the scientific productions related to the conceptions and practices of health professionals in the face of sexual and gender diversity in health care services, for this, an integrative literature review was used. Literature findings revealed the existence of concepts and practices that do not contemplate sexual and gender diversity; inadequate conceptions were associated with a distorted social-naturalizing, human-blaming and theoretical-conceptual vision, while inadequate practices were associated with a medico-biologicist, invisible technical-interventionist and normative-therapeutic practices.